Morphology and dielectric properties of polymer dispersed liquid crystal with magnetic nanoparticles - Kopčanský, P.; Timko, M.; Mitrova, Z.; Zavisova, V.; Koneracká, M.; Tomašovičov, N.; Tomčo, L.; Gornitska, O.P.; Kovalchuk, O.V.; Bykov, V.M.; Kovalchuk, T.M.; Studenyak, I.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
It has been shown that introduction of magnetic nanoparticles (MN) of various shapes with the concentration 10⁻¹ wt.% into polymer dispersed liquid crystal (PDLC) causes two effects: the size of liquid crystal droplets decreases, and the amount of the latter with through holes increases. MN increase the effective value of permittivity by more than one order within the frequency range 10⁻¹⁺ -10² HZ , as well as the electron and ion components of conductivity. MN reduce the exponent in the frequency dependence of the electron component of conductivity. The changes caused by the presence of the nanoparticles quantitatively depend on their shape.